Efektivitas Manajemen Tenaga Kependidikan di SMP Negeri 40 Surabaya - Zamzami, Ma’in; Retno Imtiyaz, Adelia; Windasari, Windasari; Hanivia Cindy, Agustin (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze the effectiveness of education staff management at SMPN 40 Surabaya. Effective education personnel management has an important role in ensuring the provision of quality education in schools. Management of educational staff at SMPN 40 Surabaya has reached an adequate level of effectiveness. Factors that have contributed to the effectiveness of education personnel management include strong leadership, effective communication, professional development, and good human resource management. Professional development of educational staff at SMPN 40 Surabaya is the main focus in increasing the effectiveness of educational staff management by holding continuous training and development programs to improve the competence of teachers and staff. Good human resource management, including appropriate assignments, rewards and recognition of good performance also contributes to the effectiveness of educational staff management.